The scientific case and the urgent need for a Prosocial Orthosociology - Koenraad Priels (Journal of Critical Realism in Socio-Economics (JOCRISE), 2023)
More and more scientific evidence shows that the primary source of societal harms and human suffering throughout history is rooted in the dominance of a Psychopathic Ruling Class. As we are witnessing the rise of a totalitarian, neo-fascist world order, there is an urgent need for a Prosocial Orthosociology: a holistic, critical, inter-and transdisciplinary, evidence based scientific research method to scrutinise all social structures from a human rights perspective. This evidence based holistic approach is aimed at exposing and eliminating anti-social, abusive, exploitative and harmful policies as an ethical imperative towards global justice and global health; with a primary focus on the Psychopathic Ruling Class, in order to address the very root problem